AN INVESTIGATION OF CRIMES RATES USING CO-KRIGING AND INVERSE DISTANCE WEIGHTS IN KATSINA STATE, NIGERIA - Usman, Umar; Suleiman, Shamsuddeen; Bui, Muhd A.; Yar'adua, Idris Shamahuddeen (FUDMA Journal of Sciences, 2021)
The aim of the study is to investigates and predict the spatial variability of crimes rates using Co-kriging and inverse Distance Weight (IDW) in ten (10) Selected Local Government in Katsina State. The reported crimes to the Katsina State Police Command Consists of grievous hurt and Wound, Cattle rustling, Rape, Kidnapping, Assaults, Stealing and Burglary. The data is collected from Criminal Investigations Department Unit in Katsina State Command from 2010 to 2019. The method applied for this study was Co- Kriging Model (CK) and Inverse Distance Weight (IDW) to test the fitted Variogram Model and Spatial dependencies of variables examined. The findings predicted that, from the study areas the crimes rates likely happen in Dantamba, Sheme, Dofar-Mato, Gunya, Dankar, Rubau, Sawai, Wurma, Birinya Tsakatsa, Dankamtsa, Gardawa, and Katsalle Villages in a long run. The results also confirmed that, high level of unemployed youth and poverty rate in the study areas have a positive impact on socio-economic factors that influenced the crimes rates. The study suggests Government should encourage the youth in such localities by providing social amenities, employment opportunities, Good education, access of Road, Nearby Police stations and police outpost should be provided in each study areas. Peaceful campaign programs on dangers of Drug abuse and Trafficking, Illegal sects and sensitization of the communities on the need for peaceful co-existence. The study suggests the Government to put more emphasis on border patrol especially Kaduna, Niger, Sokoto, and Zamfara to avoid the such occurrence of crimes in the State and Local